THE RELATIONSHIP BETWEEN FEAR OF MISSING OUT (FOMO) AND SELF-EFFICACY AT THE LEVEL OF STUDENT ORGANIZATION PARTICIPATION - Badar Fadlan Ibrahim; Dwi Rahmayani; Dewi Karisma; Selviana Diah Utami; Riska Widya Sabita; Aulia Gita Safitri (Jurnal REP (Riset Ekonomi Pembangunan), 2024)
Self-efficacy is a belief in a person's ability to achieve and improve life achievements. Therefore, individuals need to have a good level of self-efficacy. Self-efficacy supports being confident in socializing, especially in the campus environment. However, the idea of joining an organization raises the fear of not completing the study period on time, causing student participation rates in joining organizations on campus to decrease. This research aims to analyze the influence of factors that influence students' interest in joining an organization on campus. Utility theory is used as the theoretical basis for this research. The methodology used in this research is quantitative, with primary data obtained through random sampling techniques taken from 264 respondents in the Semarang City area. This research uses a logistic regression approach with a logit model in its estimation. The results of this study show that students with a higher grade (GPA), higher living costs, more free time, a higher level of Fear of Missing Out (FoMO), and a higher level of self-efficacy tend to be more likely to join campus organizations. This shows that the variables above positively influence interest in joining an organization. Therefore, choosing an organization that suits our interests, talents, and goals can increase self-efficacy because we will feel more competent, confident, and motivated to work together.